Chinese text compression algorithm based on LZW - Chen Wei; Xu Dewu; Fu Minfeng (2010 International Conference on Computer Application and System Modeling (ICCASM 2010), 2010)
This paper introduced an improved LZW algorithm of data comp- ression. In view of Chinese text charac- teristic, in this paper, the expansion to the dictionary was carried on, and the first level database of Chinese was added, with some second level of Chinese charac- ters space reserved to improve the dictionary memory method as well as the renewal way which was improved by experiments to the improvements of compression ratio.